STUDIES ON ANTIBODY-PRODUCING CELLS : I. ULTRASTRUCTURE OF 19S AND 7S ANTIBODY-PRODUCING CELLS - Gudat, Fred G. (The Rockefeller University Press, 1970)
Antibody-bearing cells of spleen and lymph node of the mouse and rabbit detected by rosette formation with the antigenic red blood cells were collected by micropipet and studied by electron microscopy. More than 300 such cells were examined. In the lymph nodes, rosette-forming cells were all in the lymphocytic and plasmacytic categories. In cells of the mouse spleen, macrophages were also found among the RFC, especially in the later days after immunization. The great majority of the RFC, 70–100%, were of the lymphocytic category. These included small, medium, and large lymphocytes with fine gradations of differentiation, and blast forms with little heterochromatin. The endoplasmic reticulum of these cells occurred in short, very narrow pieces, usually in contact with a mitochondrion. The cells of the plasmacytic category also showed fine gradations from plasmablasts to typical mature plasma cells. Plaque-forming cells of mouse and rabbit were also collected by micropipet. Of 162 such cells, fine gradations were also found throughout the lymphocytic and plasmacytic categories, but in this case the great majority were in the plasmacytic group, and more plasma cells showed amorphous nuclear chromatin. Among antibody-forming cells detected by both reactions, some of the more highly differentiated large lymphocytes contained ER which differed from that in the other large lymphocytes in that the channels were slightly and variably distended, with deposition of some precipitate, and with some tendency to a more nearly parallel orientation of the few channels seen. These were considered transitional cells. Of 10 RFC found in mitosis, all were in the lymphocytic category, in various stages of differentiation, the most advanced of which (in 2 of the 10 cells) was that of the transitional lymphocyte described here. Cells producing plaques facilitated by antisera vs. IgG of the mouse or rabbit (7S) showed the same distribution between cell categories and the same fine gradations as the direct (19S) PFC. Cells producing rosettes which were resistant to lysis in the presence of complement, and were thus presumably producing 7S antibody, showed a distribution similar to that found generally with rosette-forming cells, approximately 80–90% in the lymphocytic category.